Anaerobic biodegradation of phenanthrene by a newly isolated nitrate‐dependent Achromobacter denitrificans strain PheN1 and exploration of the biotransformation processes by metabolite and genome analyses. (7th September 2020) - Zhang, Zuotao; Sun, Jiao; Guo, Haijiao; Wang, Chongyang; Fang, Tingting; Rogers, Matthew J.; He, Jianzhong; Wang, Hui
Summary: Polycyclic aromatic hydrocarbons (PAHs) are widespread and harmful contaminants and are more persistent under anaerobic conditions. The bioremediation of PAHs in anaerobic zones has been enhanced by treating the contamination with nitrate, which is thermodynamically favourable, cost‐effective, and highly soluble. However, anaerobic PAHs biotransformation processes that employ nitrate as an electron acceptor have not been fully explored. In this study, we investigated the anaerobic biotransformation of PAHs by strain PheN1, a newly isolated phenanthrene‐degrading denitrifier, using phenanthrene as a model compound. PheN1 is phylogenetically closely related to Achromobacter denitrificans and reduces nitrate to nitrite (not N2 ) during the anaerobic phenanthrene degradation process. Phenanthrene biotransformation processes were detected using gas chromatography–mass spectrometry and were further examined by reverse transcription‐quantitative PCR and genome analyses. Carboxylation and methylation were both found to be the initial steps in the phenanthrene degradation process. Downstream biotransformation processed benzene compounds and cyclohexane derivatives. This study describes the isolation of an anaerobic phenanthrene‐degrading bacterium along with the pure‐culture evidence of phenanthrene biotransformation processes with nitrate as an electron acceptor. The findings in this study can improve our understanding of anaerobic PAHs biodegradation processes and guide PAHs bioremediation by adding nitrate to anaerobic environments.